2012
DOI: 10.1136/bjsports-2012-091129
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency denervation of the inguinal ligament for the treatment of ‘Sportsman's Hernia’: a pilot study

Abstract: This novel technique could help athletes suffering from chronic groin pain return to play more quickly, both facilitating and allowing deferral of remedial physiotherapy treatments, and potentially avoiding the need for surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 37 publications
0
34
0
Order By: Relevance
“…There are several randomised trials in the area of groin injury but they mostly cover conservative treatment or prevention of adductor-related groin pain and are summarised in table 3 34–37…”
Section: Radiological Intervention Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several randomised trials in the area of groin injury but they mostly cover conservative treatment or prevention of adductor-related groin pain and are summarised in table 3 34–37…”
Section: Radiological Intervention Techniquesmentioning
confidence: 99%
“…A more recent randomised trial from Australia hypothesised that inflammation and compression around the ilioinguinal nerve was the most likely cause of chronic groin pain in athletes and consequently constructed a study examining the effects of radiofrequency denervation (RFD) of the inguinal ligament compared to local anaesthesia and steroid injections in 36 patients 37. This study showed a significantly improved benefit in terms of pain with the use of RFD (p<0.001) with a subgroup of patients finding further short-term improvement from RFD if surgery had failed 37…”
Section: Radiological Intervention Techniquesmentioning
confidence: 99%
“…A secondary aim was to discuss the anatomical reclassification of the inguinal ligament to a tendon based on the above information and drawing from structural and functional evidence supporting this argument. The hypothesis was that direct inguinal ligament tenotomy [13, 19] or radiofrequency denervation (RFD) [4, 20] would be clinically beneficial in the context of ID management in athletes and that the published literature would support the reclassification of the inguinal ligament to a tendon.…”
Section: Introductionmentioning
confidence: 99%
“…3,18,32,35 Radiofrequency denervation of the inguinal nerve and inguinal ligament as both a primary treatment and for refractory pain after prior AP surgery has recently been described in athletes, with encouraging results up to 6 months postprocedure. 8 …”
mentioning
confidence: 99%